Effect of Yellow Sweet Potato Substitution and Egg Yolk Amount in Making Wet Noodles: - - Paramuji, Muji; Wanbahroni Jiwar Barus,; Miranti,; Aprilawati Sitompul,; Muhammad Nuh,; Eka Ayutiningsih, (Jurnal Online Pertanian Tropik, 2023)
Most of the noodles are made from wheat flour, for countries that do not produce wheat this is a problem because the need for wheat must be imported and generates a large amount of foreign exchange. This situation resulted in research involving the use of non-wheat flour or mixing wheat flour with other flour to produce noodles. This study aims to determine the effect of the substitution of wheat flour with yellow sweet potato and the amount of egg yolk in the manufacture of wet noodles. The study used a factorial completely randomized design (CRD), which consisted of two factors, namely: substitution of wheat flour with yellow sweet potato with the code "U" consisting of 4 levels; U1 = 10 %; U2 = 20 %; U3 = 30 %; U4 = 40 %. Egg yolk amount, and with code "T" which consists of 4 levels; T1 = 5 %, T2 = 10 %, T3 = 15 %, and T4 = 20 %. Parameters observed were yield, protein content, moisture content, stretchability, and organoleptic test of texture, color, and taste. The research was carried out at the UISU Faculty of Agriculture laboratory, Medan. The main ingredient used in this research is yellow sweet potato. The results of statistical analysis on each parameter concluded that the substitution of wheat flour with yellow sweet potato had a very significant effect (P<0.01) on the yield, protein content, water content, tensile strength value, organoleptic texture, color, and taste of noodles. Wet. The amount of yolk dose had a very significant effect (P<0.01) on protein content, moisture content, tensile strength value, organoleptic texture, color, and taste of wet noodles. The two treatment factors did not show any interaction. To produce wet noodles with the best quality, you can substitute up to 30% wheat flour with yellow sweet potato and use 20% egg yolk.